HYGIENIC ASSESSMENT OF LOW-CARBOHYDRATE DIET’S INFLUENCE ON THE NUTRITIONAL STATUS OF THE STUDENT - Herasymenko , S.V.; Blagaia , A.V.; Zinchenko , T.I. (The Ukrainian Scientific Medical Youth Journal, 2018)
The effect of low-carbohydrate diets on the nutritional status of human has been studied.The aim of the work was the hygienic assessment of the effect of low-carbohydrate diet on the student’s nutritional status.Materials and methods. The analysis of the nutrient composition of the four diets was carried out and the dynamics of the student’s body mass over the observation period were studied.Results. Findings indicate reduced amounts of fats and carbohydrates content in proposed diets, as well as a decrease in the level of micronutrients such as Ca, however, the amount of Mg, P, K, Fe and some vitamins were increased. The energy value of the rations was below daily needs by almost 5 times. The positive dynamics of the student’s body weight reduction for the period from 07/30/2018 to 08/22/2018 was revealed. It is determined that the fat content, incl. visceral, during the study period decreased. A decrease in chest, waist, abdomen and hips circumferences was also noted.Conclusions. The results obtained allowed to establish that a temporary low-carbohydrate diet has a positive effect on the nutritional status of a person with an increased body mass.